Managerial Leadership of School Principals in Empowering Education Personnel at SMP Negeri 4 Jombang - Kustomo, Kustomo (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to explore the role of managerial leadership by school principals in the empowerment of educational staff at SMP Negeri 4 Jombang. Using a qualitative approach and descriptive method, the research collected data through observations, interviews, and documentation to provide an in-depth understanding of the practices and strategies implemented by the principal. The findings reveal that the principal plays a crucial role in enhancing the competence and motivation of educational staff. Through structured training, participative approaches, and effective communication, the principal has successfully created a supportive and productive work environment. Analysis based on competency theory, Herzberg's motivation theory, transformational leadership theory, and classical management theory by Fayol demonstrates that a holistic and systematic approach to management and empowerment can improve educational quality and overall school performance. This study provides valuable insights for school principals and education managers on effective strategies for empowering educational staff and achieving higher educational goals.